Magical Bricks and the Bricks of Birth - Roth, Ann Macy (The journal of Egyptian archaeology, 2002)
Four mud-bricks inscribed with spells from Chapter 151 of the Book of the Dead are often found in the burial chambers of royal and elite tombs dating from the New Kingdom. These bricks can be shown to represent the four bricks that supported women during childbirth. The use of bricks in a mortuary context is thus metaphorical, replicating the equipment of an earthly birth in order to ensure the deceased's rebirth into the other world. Such bricks may also have been used in the ‘Opening of the Mouth’ ritual, both at funerals and in temple foundation ceremonies. In connection with their role at birth, bricks also appear at the judgment a person faced after death. Like other artifacts surrounding birth in Egypt, bricks of birth had parallels in ancient Mesopotamia.